DEVELOPMENT OF A GOODS INVENTORY INFORMATION SYSTEM AT DARUL ULUM ISLAMIC SCHOOL BANDA ACEH BASED ON CODEIGNITER - Sufyan; Syibral Malasyi; Adi Ahmad; Maimun; Riyan Maulana (CV Naskah Aceh, 2023)
Darul Ulum Islamic Middle School Banda Aceh which has goods that must be managed well, quality and availability maintained. Inventory items must be managed and data well so that all inventory items are recorded in a system called Development of an Inventory Information System at Darul Ulum Islamic Middle School in Banda Aceh based on CodeIgniter. There are important inventory items that must be recorded in each room so that all inventory is recorded and handled properly. The inventory system currently used cannot display inventory history, the search for tools and goods is still manual, and the condition of the inventory items is not detected or is no longer suitable for use. The CodeIgniter-based inventory information system is a system that the author created to facilitate the performance of employees at Darul Ulum Islamic Middle School in Banda Aceh in managing inventory. Inventory data becomes more effective, efficient and data recapitulation is more accurate. The output from this system is in the form of inventory reports, user reports and item conditions.